A Formação em informação e documentação: Portugal na contemporaneidade - Maria Manuela Gomes de Azevedo Pinto (2008)
We intend to analyze and situate the current state of education in Information and Documentation in Portugal, referring a whole evolutionary process, either in the international context, or in the national one, whichwill allow us to identify actuation paradigms and the complex moment of change caused by the emergence of theInformation Society and of a new scientific area - the Information Science. Facing a clear domain of professionalpractices in the education models, nowadays a new effort is being developed, still not generally, which aims to givethem an epistemological and theoretical support that allows answering to the dynamics of the challenges created by contemporary society and to guarantee either a scientific consolidation, or an adequate professional performance, in order to solve an identity crisis worsened by the autonomic tendencies of disciplinary areas, such as Library Science, Documentation and Archival Science, focused in the custody, in the technique and in the document and built since the end of the 19th century. It is in the second half of the 20th century that emerges the scientific-informational paradigm, focused in the information, and under which are being structured innovative models of education and scientific research that cohabit, however, with traditional ones, in the general context of a supposed deep reflectionwhich would sustain the unsurpassable "adaptation to Bologna" of the high level education.